SERVICE QUALITY, BRAND IMAGE AND PRICE FAIRNESS IMPACT ON THE CUSTOMER STATISFACTION AND LOYALTY TOWARDS GRAB BIKE - Gusti Noorlitaria Achmad; Adinda N Nisha; Yusniar Yusniar; Mochamad Ridwan (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
Abstract: This study aims to analyze and explain the Effect of Service Quality, Brand Image, and Price Fairness Impact on Customer Satisfaction and Loyalty; The population used in this study are all customers who have used Grab Bike services, aged 17 years, and located in Samarinda City, with a total sample of 100 people. The data collection technique uses non-profitability sampling, the analysis is carried out using Partial Least Square (PLS) with the SmartPLS application version 3.8.9. The results showed that: Service quality has a positive and insignificant effect on customer satisfaction; Service Quality has a positive and insignificant effect on loyalty; Brand Image has a positive and significant effect on customer satisfaction; Brand Image has a positive and significant effect on loyalty; Price Fairness has a positive and significant effect on Customer Satisfaction; Price Fairness has a positive and significant effect on Loyalty; Customer Satisfaction has a positive and significant effect on Loyalty. Keywords: Service Quality, Brand Image, Price fairness, Customer Satisfaction and Loyalty Toward.